Distribution, migration and changes of typical chemical preservatives on orange during storage and processing. (30th July 2023) - Zhang, Mengna; Pan, Xinglu; Dong, Fengshou; Liu, Na; An, Xiaokang; Wang, Liping; Xu, Jun; Wu, Xiaohu; Zheng, Yongquan
Highlights: A modified QuEChERS was developed and validated for sample pretreatment. The distribution ability of preservatives correlated positively with their log P. Preservatives intra-fruit transferability was inversely related to their log P. Orange juice and pectin processing removed pesticide residues by 41.4–98.6%. Dietary risk exposure to tangerine peel and essential oil should arose attention. Abstract: To evaluate the safety of orange treated with preservatives, we analyzed the distribution, migration and changes of the three most common preservatives (prochloraz, imazalil, and thiophanate-methyl) during orange storage and processing. After treatment, preservatives entered orange rapidly within 2 h, and with the greatest levels being in the outer yellow peel, followed by the stem, middle white peel, and finally pulp. The intra-fruit migration ability of the three preservatives correlated inversely with their octanol/water partition coefficients. Residual preservatives and their metabolites in orange pulp were less than 0.84 mg/kg in storage duration. Orange juice and pectin processing could effectively remove the residues, with processing factors (PFs) of 0.159–0.446 and 0.014–0.059. For tangerine peel, however, the process increased the levels of residual preservatives with PFs of 2.964–6.004. Therefore, concern is warranted with regard to the risk of dietary exposure to tangerine peel and essential oil.